Protease inhibitors of Cajanus conferring resistance to pod borer of pigeonpea (Cajanus cajan L. Millsp.) - Sandhya Srikanth (Electronic Journal of Plant Breeding, 2017)
Pigeonpea is susceptible to pod borer damage with resistance lacking in its primary gene pool. Many Cajanus species harbor high levels of resistance. Host plant resistance can play an important role in minimizing the extent of losses due to insects and pests as well as the use of insecticides/pesticides and thus protect the environment. A major initiative was undertaken to tap the defence genes from wild relatives of secondary and tertiary gene pool through wide hybridization and thereby introgress resistance to pod borer. A range of interspecific derivatives derived from C. lanceolatus, C. cajanifolius, C. volubilis and C. platycarpus along with their parents were screened for the pod borer resistance under unprotected field conditions at ICRISAT, Patancheru, India. Biochemical basis of resistance was also identified by studying the levels of defence proteins active against bovine pancreatic trypsin, chymotrypsin and trypsin-like enzymes of H. armigera mid-gut proteases. Protease inhibitor profiles of parents and interspecific derivatives differed in terms of activity units, number and intensities of activity bands visualized on gelatin-PAGE. As the protease inhibitors are anti-nutritional factors, parents and interspecific derivatives, which resulted in high levels of Helicoverpa gut protease inhibitor (HGPI) units were screened for Human pancreatic trypsin inhibitor (HPTI) activity levels. Samples with high ratio of HGPI/HPTI represent less or no effect on human pancreatic trypsin and high effect on insect gut proteases.